"Drinking from Our Own Wells": Tongshik Ryu's P'ungryu Christian identity. Issue 1 (28th February 2022) - Kaunda, Chammah J.
Abstract: This article is written in honor of Tongshik Ryu (Tong‐sik Yu), a thinker who has greatly contributed and influenced the shaping of Korean indigenous theology. It takes an appreciative historical reconstruction of his Korean cultural theology of P'ungryudo. It argues that to fully appreciate and understand Ryu, we must give attention to his personal experiences and the cultural crisis of his time. Ryu was born and raised in the context of Japanese colonization in which Korean cultural identity was mutilated and was in constant danger of being obliterated. He deployed P'ungryu as a cultural framework to make sense of how Christianity which was becoming a dominant religion could be entrenched within the Korean cultural system. By appealing to the P'ungryu cultural system, Ryu unquestionably demonstrated that Korean people would become authentic Koreans by achieving recovery of their cultural identity and out of it reconstruct themselves for the contemporary situation and participate adequately in the universal task of humanity's continuous creation of "the one planetary beautiful life."